Hubungan Kekerabatan Bahasa Aceh, Bahasa Devayan, Bahasa Sigulai, dan Bahasa Jamee - Sitti Rahmah Muhammad; Hendrokumoro Hendrokumoro (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study investigates the percentage of kinship level, separation time, and phonemic correspondence among Acehnese, Devayan, Sigulai, and Jamee languages by applying theories from Keraf (1996) and Crowley & Bowern (2010). Data was collected using interviewing, recording, listening, and note-taking techniques. Data analysis applied lexicostatistics and glottochronology techniques. The study's results indicated that Acehnese, Devayan, Sigulai, and Jamee languages were related. Based on the results of lexicostatistical calculations, it is known that the Acehnese-Devayan language, Acehnese-Jamee language, Devayan-Sigulai language, Devayan-Jamee language, and Sigulai-Jamee language can be grouped into (family) while Acehnese-Sigulai language is at the (stock) level. Acehnese and Devayan languages were a single language estimated between 2,054-2,458 years ago. Acehnese and Sigulai languages were a single language around 3,169-3,420 years ago, Acehnese and Jamee languages were a single language in 1,836 -2,206 years ago, Devayan and Sigulai languages were a single language in 1945 -2283 years ago, Devayan and Jamee were a single language in 2114-2,316 years ago, Sigulai and Jamee were a single language between 2,010-2.404 years ago. In addition, phonemic correspondences were also found within the four languages.